Actualización del tratamiento de las infecciones de vías urinarias en gestantes. - Espinoza Parraga, Jaime Andres (Machala : Universidad Técnica de Machala, 2024)
Urinary tract infection is one of the main pathologies that affect normal development during the gestation period; it occurs in up to 50% of women during life. However, in pregnant women it persists in 22.7% due to changes in their function and anatomy which cause serious alterations due to not evaluating or initiating treatment. Complications that can be prevented by starting pharmacological measures must be considered to avoid irreversible damage such as threat of preterm birth, increased incidence of preterm birth with low birth weight. Objective: Identify the treatment of urinary tract infection in pregnant women. Methodology: Descriptive category study, of qualitative nature where the search for scientific articles of great impact in the medical area is carried out through the use of Medical Subject Headings (MESH), the terminology was chosen, and the search in journals such as PUBMED, ELSEVIER , Taylos&Francis or in search engines of academic prestige with the intention of increasing knowledge about the subject matter. Conclusion: In the treatment of the urinary tract according to the guidelines, urine culture should be assessed as an adequate diagnosis, which shows sensitivity and specificity, so that antibiotic prescription thus avoids bacterial resistance. Management is individualized with respect to the trimester in which the pregnant patient is studying. Treatment of asymptomatic bacteriuria is with nitrofurantoin, cephalexin, amoxicillin, amoxicillin/clavulanic acid, cystitis with fosfomycin, nitrofurantoin, amoxicillin/clavulanic acid, cefuroxime, and pyelonephritis with ceftriaxone, cefazolin, and cephalexin.
La infección de vías urinarias está inmersa en las principales patologías que afectan el desarrollo normal durante el periodo de gestación, se presenta hasta en el 50% de las mujeres durante el periodo vida. Sin embargo, en gestantes persiste un 22.7% debido a cambios en su función y anatomía los cuales ocasionan alteraciones de gravedad por no valorar o iniciar tratamiento. Se debe considerar las complicaciones que se puede prevenir al iniciar con las medidas farmacológicas para evitar daños irreversibles como amenaza de parto pretérmino, aumento de la incidencia de prematuro con bajo peso al nacer. Objetivo: Identificar el tratamiento de la infección de vías urinarias en las gestantes. Metodología: Estudio de categoría descriptiva, de carácter cualitativo en donde se procede la búsqueda de artículos científicos de gran impacto en el área médica mediante el uso de Medical Subject Headings (MESH) se escogió la terminología, y el rastreo en revistas como PUBMED, ELSEVIER, Taylos&Francis o en buscadores de prestigio académico con la intención de engrandecer el conocimiento acerca del tema conformado. Conclusión: El tratamiento de las vías urinarias según las guías, se debe valorar el urocultivo como diagnóstico adecuado, el cual muestra sensibilidad y especificidad, de tal forma que la prescripción antibiótica, evita así resistencia bacteriana. El manejo es individualizado respecto al trimestre en cual esté cursando la paciente gestante. El tratamiento de la bacteriuria asintomática es con nitrofurantoína, cefalexina, amoxicilina, amoxicilina/ácido clavulánico, la cistitis con fosfomicina, nitrofurantoína, amoxicilina/ácido clavulánico, cefuroxima y la pielonefritis con ceftriaxona, cefazolina y cefalexina.
Keywords: GESTANTES; AGENTE ETIOLOGICO; ANTIBIOTICOS; TRACTO URINARIO